HUKUM NIKAH ONLINE MENURUT AHLI FIKIH KONTEMPORER - Wahyudin, Yuyu; Nurhayati , Isti (An Nawawi, 2024)
Advances in science and technology have changed many human behaviors. In the past, marriage contracts were carried out at The Religious Affires Office, at mosque, at home and at the hotel, face to face, and in one place, followed by the groom and bride, the bride's guardians, two witnesses, civil registration officer from the local Religious Affires Office, extended family members of the groom and bride and invited guests. At the moment, By using the internet, it is possible to carry out the marriage contract online via zoom, google meet, video call, and other semilir media. The bride's guardian conveys the consent to the groom, because the groom is outside the island or even abroad, this happens for several reasons, for example due to administrative problems, there is a ban on gathering in large numbers, there are government regulations to maintain distance when interacting and communicating due to the Covid 19 outbreak and other reasons. There for, discussion about online marriage is very important. The purpose of writing this article is so that the muslim community knows the meaning and law of carrying out an online marriage. So that the Muslim community can obtain legal certainty in accordance with Islamic law regarding online marriages. So that it becomes a guide for the Muslim community in carrying out online marriages. The method used in this research is a qualitative approach. Researchers will also use a library study approach towards the books of the four madhhab imams and contemporary fiqh books. The formulation of the problem is: 'What is the law on online marriage according to the contemporary fiqh expert?